PP.05.05: PREDICTIVE VALUE OF LEPTIN AND ADIPONECTIN-TO-LEPTIN RATIO FOR HYPERTENSION AND INSULIN RESISTANCE IN SUBJECTS WITH LOW CARDIOVASCULAR RISK. (June 2015) - Ivkovic, V.; Kos, J.; Karanovic, S.; Lela, I. Vukovic; Premuzic, V.; Dika, Z.; Laganovic, M.; Pecin, I.; Fucek, M.; Simicevic, L.; Sertic, J.; Vrdoljak, A.; et al.
Abstract : Objective: Leptin is an important predictor of cardiovascular (CV) risk. Some studies found that adiponectin-to-leptin ratio (A/L) is a better predictor of hypertension (HT) and insulin resistance (IR) than leptin alone. Our goal was to evaluate whether A/L improves the predictive value of leptin for HT and IR in subjects with low cardiovascular risk. Design and method: Participants (N = 208; 135 females; 171 normotensives (NT) and 37 untreated HT (uHT) were selected from a random sample of 2487 subjects enrolled in cross-sectional study, Subjects with diabetes, chronic kidney disease, pregnancy, terminal illness and treated hypertensives were excluded. BP was measured using Omron M6 device following ESH/ESC guidelines. IR was defined as HOMA-IR>3. Adiponectin and leptin concentrations were determined by ELISA. Results: There were 147 insulin resistant (IR), 61 non-IR subjects. Leptin concentration was lower in NT than in HT (11.05 (5.85–16.75) vs. 8.44 (3.60–14.61), p = 0.05), while there was no difference in A/L (p = 0.56). Leptin was significantly higher in IR than non-IR subjects (12.00 (6.00–17.50) vs. 7.64 (3.25–13.64), p = 0.002) while A/L was lower (0.73 (0.43–1.12) vs. 1.35 (0.59–3.20), p < 0.001). Using receiver operating curves (ROC) to examine the predictive value of leptin and A/L for HT and IR we found that leptin values>5.4 ug/L had a sensitivity of 81% and specificity of 34% for HT (AUC = 0.604, p = 0.04), while A/L was not a significant predictor of HT (AUC = 0.531, p = 0.53). Conclusions: Untreated HT significantly differ from NT in leptin but not in A/L values. However, neither leptin nor A/L are sufficiently significant predictors of HT and IR in subjects with low cardiovascular risk.